All-fiber femtosecond laser providing 9 nJ, 50 MHz pulses at 1650 nm for three-photon microscopy. (30th May 2017) - Cadroas, P; Abdeladim, L; Kotov, L; Likhachev, M; Lipatov, D; Gaponov, D; Hideur, A; Tang, M; Livet, J; Supatto, W; Beaurepaire, E; Février, S
Abstract: The spectral window lying between 1.6 and 1.7 μ m is interesting for in-depth multiphoton microscopy of intact tissues due to reduced scattering and absorption in this wavelength range. However, wide adoption of this excitation range will rely on the availability of robust and cost-effective high peak power pulsed lasers operating at these wavelengths. In this communication, we report on a monolithically integrated high repetition rate (50 MHz) all-fiber femtosecond laser based on a soliton self-frequency shift providing 9 nJ, 75 fs pulses at 1650 nm. We illustrate its potential for biological microscopy by recording three-photon-excited fluorescence and third-harmonic generation images of mouse nervous tissue and developing Drosophila embryos labeled with a red fluorescent protein.